2010
DOI: 10.1088/0031-8949/2010/t140/014011
|View full text |Cite
|
Sign up to set email alerts
|

Conditional generation of optical Schrödinger cat states

Abstract: Given a source of two coherent state superpositions with small separation in a traveling wave optical setting, we show that by interference and balanced homodyne measurement it is possible to conditionally prepare a symmetrically placed superposition of coherent states around the origo of the phase space. The separation of the coherent states in the superposition will be amplified during the process.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…These experimental schemes contain only beam splitters and homodyne detectors, and they are capable of producing coherent-state superpositions in traveling fields along the real axis and on an equidistant lattice in the phase space. These schemes are based on an apparatus developed previously for generating Schrödinger cat states [81]. It has been shown that the proposed setups can generate amplitude squeezed states, binomial states, squeezed cat states, and various photon-number superpositions with high fidelities and with success probabilities that can be sufficient for practical applications.…”
Section: Special Coherent-state Representationsmentioning
confidence: 99%
“…These experimental schemes contain only beam splitters and homodyne detectors, and they are capable of producing coherent-state superpositions in traveling fields along the real axis and on an equidistant lattice in the phase space. These schemes are based on an apparatus developed previously for generating Schrödinger cat states [81]. It has been shown that the proposed setups can generate amplitude squeezed states, binomial states, squeezed cat states, and various photon-number superpositions with high fidelities and with success probabilities that can be sufficient for practical applications.…”
Section: Special Coherent-state Representationsmentioning
confidence: 99%
“…Single-photon sources (SPS) are the key elements in numerous applications in the field of quantum information processing [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and photonic quantum technology [15][16][17][18][19]. Heralded single-photon sources (HSPS) based on spontaneous parametric down-conversion (SPDC) [20][21][22][23][24][25][26][27] and spontaneous four-wave mixing (SFWM) [28][29][30][31] are promising candidates for realizing periodic SPS.…”
Section: Introductionmentioning
confidence: 99%
“…Construction of periodic single-photon sources (PSPS) is subject to intensive research due to the numerous applications of such devices in quantum information processing [1][2][3][4][5][6][7][8][9][10][11][12][13] and photonic quantum technology [14][15][16][17][18]. The most promising realization of PSPS are the heralded single-photon sources (HSPS) based on heralding one member (termed as the signal) of a correlated photon pair generated in nonlinear optical media by detecting the other member (referred to as the idler) of the photon pair.…”
Section: Introductionmentioning
confidence: 99%